Biopolymer nanostructures for food encapsulation purposes - Jafari, Seid Mahdi (Nanoencapsulation in the food industry, 2019)
Biopolymer Nanostructures for Food Encapsulation Purposes, a volume in the Nanoencapsulation in the Food Industry series, guides readers on how to fabricate and apply nanostructures from different proteins, carbohydrates and chemical sources for food encapsulation purposes. This book covers recent and applied research in all disciplines of bioactive and nutrient delivery. Chapters emphasize original results relating to experimental, theoretical, formulations and/or applications of nano-structured biopolymers.